SHARITY: A Spare Sharing Community App - Tumibay, Jazmine Liberty J.; Nieves, Roice Mico M.; Arceo, Ezekiel P.; Villar, Galilee A.; Santos, Hilda W.; Bautista, Joshua S. (International Journal of Computing Sciences Research, 2024)
Purpose – The study aimed to create a platform that enable individuals within a community to share or lend their spare resources, request food or items from others in the community through the platform, and ensure that the web application was usable, functional, efficient, and reliable. Method – The researchers used the RAD approach which is ideally suited to adapt to changes in the applications, such as features, functionalities, and upgrades. To determine the usability, functionality, efficiency and reliability, evaluation was administered using the 5-point Likert scale. Lastly, to determine the consistency of data collected by the researchers, Cronbach's Alpha (α) was used. Results – The web and mobile applications scored highest in functionality and usability, while the app excelled in efficiency and reliability. Both web and mobile apps received positive feedback for their user-friendly interfaces and effective functionalities. Conclusion – From the design, development and series of testing, the web application was successfully developed. The platform developed allowing the users to share spare food or resources, lend/borrow items, and post requests for assistance was indeed successful. Recommendations – The researchers have only implemented SMS OTP as a security feature. It must have added security features for users to prevent their accounts from being breached and their identities from being stolen. Research Implications – The resulting data has shown that the SHARITY app can be an effective tool in promoting community engagement and collaboration in terms of sharing of foods and resources.